Managing collective trauma on social media: the role of Twitter after the 2011 Norway attacks. (April 2016) - Eriksson, Moa
This study analyses the meaning-making discourse on Twitter in the 6 days following the 2011 Norway attacks. The attacks in Oslo and on the island of Utøya resulted in 77 deaths, of which 69 were youths on Utøya, where a summer camp arranged by the Norwegian Social Democratic youth organisation Arbeidernes Ungdomsfylking (AUF) was being held. The main discursive themes in the material were found to be focused on the Norwegian nation, expressions of solidarity, the meaning and outcomes of the attacks, as well as details of the attacks themselves. These themes were of changing importance over the 6 days following the attacks, as discussions concerning the Norwegian nation and the attacks themselves dropped rapidly in favour of negotiating the explanations behind the attacks. Twitter was shown to be useful for providing backchannel discourse negotiations that were separate from the mass media discourse concerning the attacks.